ENGLISH INSTRUCTORS’ ROLE IDENTITIES AND THEIR ABILITY TO MANAGE CLASSROOM SETBACKS: THE CASE OF KYRENIA - Shoar, Sonia; Koyalan, Aylin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Teacher identity, a complex and dynamic phenomenon, is shaped by various social and institutional factors. While previous research has established teacher identity as a critical factor in educational outcomes, this study specifically examines how different aspects of professional identity influence teachers’ responses to classroom setbacks. Employing a quantitative research approach, this study investigates the role identity of English teachers through survey data. The primary objective is to explore the correlation between the professional identity of university-level English teachers and their proficiency in managing classroom setbacks. Data were gathered through surveys administered to 86 English teachers in Kyrenia, focusing on educators affiliated with FIU, GAU, GU, CSU, and ARUCAD during the 2023–2024 academic year. Two scales were utilized: "Teacher’s Ability to Manage Classroom Setbacks" and "Teacher’s Role Identity." The analysis demonstrates that English language teachers in Kyrenia maintain relatively strong professional identities across multiple dimensions, with particularly high identification in learner, pundit, and interaction supervisor roles. These findings suggest that teachers in this context view themselves primarily as continuous learners, subject matter experts, and facilitators of student interaction. The results collectively indicate that teacher identity and classroom setback management are complex, multifaceted constructs influenced more by institutional and contextual factors than by individual characteristics or general competence perceptions. While teachers demonstrate strong professional identities, the ability to manage classroom challenges appears more dependent on institutional support, specific role combinations, and environmental factors than on overall identity strength or demographic characteristics. Bridging the gap between teachers’ identity beliefs and their classroom decisions may inform interventions that foster positive school outcomes, including improved student behaviour and academic achievement.